2020
DOI: 10.1142/s0219581x21500046
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical, Ferroelectric and Magnetic Properties of NiTiO3 Ceramic Synthesized by Citrate Gel Method

Abstract: The NiTiO3 ceramic was synthesized in nanostructured form by citrate gel method. The phase structure, microstructure and magnetic properties of synthesized compounds were investigated by X-ray diffraction (XRD), scanning electron microscope and vibrating sample magnetometer. Williamson–Hall plot was used to calculate the crystallite size and microstrain of sample. The XRD analysis showed the formation of rhombohedral crystal structure of synthesized powders. The crystallite size is about 35[Formula: see text]n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The key advantage of this method is to keep the homogeneity of the starting material from solution to gel. Our group has successfully synthesized NiTiO 3 nanomaterials by the citrate method [20]. In this work, we presented the analysis of electrical properties of ilmenite NiTiO 3 which was synthesized by a simple low-cost citrate gel method…”
Section: Introductionmentioning
confidence: 99%
“…The key advantage of this method is to keep the homogeneity of the starting material from solution to gel. Our group has successfully synthesized NiTiO 3 nanomaterials by the citrate method [20]. In this work, we presented the analysis of electrical properties of ilmenite NiTiO 3 which was synthesized by a simple low-cost citrate gel method…”
Section: Introductionmentioning
confidence: 99%
“…NiTiO 3 is an semiconductor with a bandgap value ranging from 2.2 eV-2.8 eV [4] and is antiferromagnetic with a Neel temperature about −251÷−252 • C [5]. Previous reports showed that NiTiO 3 exhibited ferroelectric characteristics at room temperatures [6][7][8]. Generally, magnetic properties of NiTiO 3 ceramic can be changed by metal transition dopants [9][10][11].…”
Section: Introductionmentioning
confidence: 99%